PREDIKSI TINGKAT KEBANGKRUTAN PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2015 (DENGAN METODE Z-SCORE ALTMAN DAN Z-SCORE FOSTER) - ERWITA DEWI (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This study aims to determine the financial statements prior to the bankruptcy can be used to predict the rate of bankruptcy with Altman Model and Foster on coal mining company listed on the Indonesia Stock Exchange. Model classification Altman Z score Z score> 2.90 is classified as a healthy company, while the company has a Z score <1.20 were classified as potentially bankrupt company. Furthermore, scores between 1.20 to 2.90 is classified as a company in the gray area or the gray area. While the Model Z score Foster use the